On the Study of Visual Exploration vs. Educational Levels Using an Automated Cancellation Test - dos Santos, Suzane Santos; Campos, Erick Modesto; Figueiro, Paulo Alberto Nogueira; Pontes, Fernando Augusto Ramos; Sampaio Neto, Nelson Cruz; Mota, Marcelle Pereira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
Tests that evaluate individual strategies for visual exploration may help uncover deviations from typical cognitive developments. A subgroup of visual exploration tests, called cancellation tests, measures the ability to identify specific targets surrounded by distractors. We present an automated version of a cancellation test: the car’s test. We carried out the test evaluation in two distinct groups: high school students and a university group that is included, students and professors. Several studies indicate the influence of education level on cancellation test results. We investigated whether education and the arrangement of symbols are relevant factors in choosing the visual exploration strategy used. We hypothesize that typical users with higher education levels will tend to the horizontal linear strategy since it is associated with the reading pattern. The results analysis allowed us to confirm this hypothesis, besides revealing valuable information about statistics on visual exploration patterns.